Comparison of Surface Roughness of Class V Cavity Preparation using Diamond Abrasive Point and Ultrasonic Tip and Measurement of Shear Bond Strength after Restoration with Composite Resin: An In-vitro Study - Abhijit Ghosh; Priti D Desai; Ipsita Maity; Paromita Mazumdar (Journal of Clinical and Diagnostic Research)
Introduction: Non Carious Cervical Lesions (NCCLs) represent a prevalent dental condition characterised by the erosion of tooth structure at the cementoenamel junction without the involvement of dental caries. These lesions pose significant challenges due to their aesthetic impact, potential for dentinal hypersensitivity, plaque accumulation, pulpal complications and compromised structural integrity of the teeth. Tooth preparation traditionally uses diamond abrasive points and tungsten carbide burs for micromechanical adhesion. Newer methods, like ultrasonic tips, offer a more conservative approach, but limited research has compared their effects on bond strength, particularly in cervical cavity restorations with nanohybrid composites. Aim: To compare the surface roughness of cervical cavity preparations utilising diamond abrasive points and ultrasonic tips, and to evaluate the shear bond strength of restorations with composite resin. Materials and Methods: The present in-vitro comparative study was conducted in the Department of Conservative Dentistry and Endodontics, Guru Nanak Institute of Dental Sciences and Research, Panihati, Kolkata, West Bengal, India, from October 2023 to December 2023. The study included 52 freshly extracted maxillary 1st premolar teeth extracted for orthodontic reasons. These teeth were divided into two groups: Group-I (n=26) underwent surface preparation using a diamond abrasive point (No. 835-012, Piranha, SS White, USA), while Group-II (n=26) was prepared using an ultrasonic tip (Woodpecker G 20, Guilin Woodpecker, China). Teeth were cleaned, disinfected and stored in 0.1% thymol solution before being prepared with diamond abrasive points or ultrasonic tips, following which the specimens were restored using nanohybrid composite material (Solare X, GC Corporation, Japan). Surface roughness was assessed using a digital profilometer before the restoration, and the shear bond strength of repaired specimens was measured with a Universal Testing Machine. Statistical analysis was performed using GraphPad Prism, with independent samples t-tests applied to compare results between groups, and a significance level set at 5%. Results: Group-I exhibited greater surface roughness (6.33±2.18 μm) compared to Group-II (4.91±1.57 μm). Group-I also showed higher shear bond strength (62±13 MPa) than Group-II (59.3±19.9 MPa), though this variation was not statistically significant (p-value=0.56). Conclusion: Within the present study’s limitations, diamond abrasive points created significantly greater surface roughness compared to ultrasonic tips. However, no statistically significant variations have been observed in shear bond strength among the two methods, suggesting that ultrasonic tips may be considered as an alternative to diamond abrasive points in clinical settings, avoiding their drawbacks while achieving adequate restoration retention.